Effectiveness of school-based health education intervention on knowledge, attitude and practices in pediculosis capitis - Mohd Tohit, Nor Faiza; Muhamad Saliluddin, Suhainizam; Mun-Sann, Lye; Rampal, Lekhraj; Poh Ying, Lim (International Journal of Children, Women, Elderly and Disable People, 2019)
Pediculosis capitis can be found in any age and race although school-age children are the groups that are mostly at risk. The objective of this study was to develop, implement and evaluate the effectiveness of the health educational module based on KAP Model on the level of knowledge, attitude and practices on Pediculosis capitis among school children in Selangor. A cluster randomised controlled trial was conducted among students aged 10-11 years. Using simple random sampling, 10 schools were selected. At baseline, a validated questionnaire was given to assess their KAP level and screening for Pediculosis capitis was done. Then the schools were divided into intervention and control groups. The intervention group received approximately 3 hours of concise educational module whereas the control group only received a 30-minutes health talk on the knowledge component of the module. All the students were prescribed with pediculicides for application at home. After two-weeks, the postintervention assessment was conducted using the same questionnaires. The students were re-examined for evidence of Pediculosis capitis after treatment. A total of 4,344 students were examined and 318 students were found to be infested with Pediculosis capitis. The overall prevalence was 7.32 %. In the intervention group, only the attitude showed significant increase at 2-weeks post-intervention as compared to baseline (χ2 = 4.878, df =1, p = 0.027). Both knowledge and practice did not show significant increase of good knowledge and practice level at 2-weeks post-intervention as compared to baseline. In the control group, none of the variable showed significant increase at 2-weeks postintervention as compared to baseline. Generalized Estimating Equations (GEE) was conducted to determine the effectiveness of the educational intervention module in increasing the respondents’ KAP on Pediculosis capitis. GEE showed significant association of knowledge level and time point with group. The odds of having good knowledge in the intervention group is 1.7 times higher as compared to the control group (AOR = 1.748, 95% CI:1.006 – 3.035, p = 0.048). The odds of having good knowledge at 2-weeks postintervention was 1.1% higher as compared to baseline after adjusting for trial covariates (AOR =0 .011, 95% CI:0.006 – 0.019, p<0.001).